White matter edematous change with moderate vascular lesions in pretreated acute stage of leukoencephalopathy with cerebral amyloid angiopathy. Issue 2 (17th January 2022) - Yasuda, Ken; Ayaki, Takashi; Li, Fangzhou; Kuwata, Yasuhiro; Maki, Takakuni; Sainouchi, Makoto; Moriyoshi, Koki; Nakamura, Michikazu; Takahashi, Ryosuke
Abstract : A 79‐year‐old man presented with subacute onset of dementia. Brain magnetic resonance imaging revealed leukoencephalopathy in the posterior lobes with presence of microbleeds. Although clinical manifestation suggested a diagnosis of leukoencephalopathy associated with cerebral amyloid angiopathy (CAA), the patient died of sudden rupture of an aneurysm of the thoracic aorta two months after the onset of dementia. Autopsy revealed pathological features of advanced‐stage Alzheimer's disease. Immunohistochemistry for amyloid‐β revealed CAA mainly affecting arteries but not capillaries. Klüver–Barrera staining revealed white matter edema predominantly in the occipital lobes without ischemic changes. Perivascular cuffing was found to be sparse, but there was no evidence of angiitis. Pathological findings suggest that leukoencephalopathy was caused by the disruption of the blood–brain barrier rather than ischemia. Because the present patient died before immunotherapy, his neuropathological findings could reflect the pathomechanism of the acute stage of leukoencephalopathy with CAA.